Exploiting the diversity of tomato: the development of a phenotypically and genetically detailed germplasm collection. (1st May 2020) - Mata-Nicolás, Estefanía; Montero-Pau, Javier; Gimeno-Paez, Esther; Garcia-Carpintero, Víctor; Ziarsolo, Peio; Menda, Naama; Mueller, Lukas A; Blanca, José; Cañizares, Joaquín; van der Knaap, Esther; Díez, María José
Abstract: A collection of 163 accessions, including Solanum pimpinellifolium, Solanum lycopersicum var. cerasiforme and Solanum lycopersicum var. lycopersicum, was selected to represent the genetic and morphological variability of tomato at its centers of origin and domestication: Andean regions of Peru and Ecuador and Mesoamerica. The collection is enriched with S. lycopersicum var. cerasiforme from the Amazonian region that has not been analyzed previously nor used extensively. The collection has been morphologically characterized showing diversity for fruit, flower and vegetative traits. Their genomes were sequenced in the Varitome project and are publicly available (solgenomics.net/projects/varitome ). The identified SNPs have been annotated with respect to their impact and a total number of 37, 974 out of 19, 364, 146 SNPs have been described as high impact by the SnpEeff analysis. GWAS has shown associations for different traits, demonstrating the potential of this collection for this kind of analysis. We have not only identified known QTLs and genes, but also new regions associated with traits such as fruit color, number of flowers per inflorescence or inflorescence architecture. To speed up and facilitate the use of this information, F2 populations were constructed by crossing the whole collection with three different parents. This F2 collection is useful for testing SNPs identified by GWAs, selection sweeps or any other candidate gene. All data is available on Solanaceae Genomics Network and the accession and F2 seeds are freely available at COMAV and at TGRC genebanks. All these resources together make this collection a good candidate for genetic studies.